Cognitive and behavioral predictors of procrastination behavior in adolescents at a mental health clinic in Turkey - GÜNDOĞDU, ÜMMÜGÜLSÜM (My University, 2022)
Objective: Procrastination behavior (PB) negatively impacts individuals’ daily lives. Based on existing evidence that states executive function (EF) problems and internalizing symptoms (IS) are related to PB, this study examined IS, EF problems, and sluggish cognitive tempo (SCT) symptoms in adolescents, and their relationships with PB and gender. Methods: The sample consisted of 78 adolescents (56.4% female) aged 12–18 years. Participants and their families completed the Children’s Depression Inventory (CDI), Screen for Child Anxiety Related Disorders (SCARED), Barkley Sluggish Cognitive Tempo Scale-Children and Adolescent (BSCTS-CA), General and Academic Procrastination Scales, Behavior Rating Inventory of Executive Function (BRIEF), and Strengths and Difficulties Questionnaire (SDQ). Results: The scores for academic PB were significantly positively associated with the CDI, SCARED, subscales comprising the metacognitive index of the BRIEF, and all four subscales of the SDQ but not with SCT. General and academic PB yielded similar results except for the conduct problems. Academic PB and EF problems were more prevalent in males. Lack of organizational skills, a part of EF; IS; and attention problems were associated with academic and general PB in girls and boys. Conclusion: Adolescents who have difficulty organizing their work and attention problems may have higher PB.
Keywords: Sosyal ve Beşeri Bilimler; Psikoloji; Gelişim Psikolojisi; Klinik Psikolojisi; Sağlık Bilimleri; Social Sciences and Humanities; Psychology; Developmental Psychology; Clinical Psychology; Health Sciences; PSİKOLOJİ, KLİNİK; Temel Bilimler (SCI); PSİKOLOJİ, GELİŞTİRME; Psikiyatri; Klinik Tıp (MED); PSYCHOLOGY, CLINICAL; PSYCHOLOGY; Natural Sciences (SCI); PSYCHOLOGY, DEVELOPMENTAL; PSYCHIATRY; Clinical Medicine (MED); Gelişim ve Eğitim Psikolojisi; Klinik Psikoloji; Psikoloji (çeşitli); Genel Psikoloji; Psikiyatrik Ruh Sağlığı; Psikiyatri ve Ruh Sağlığı; Sosyal Bilimler ve Beşeri Bilimler; Developmental and Educational Psychology; Psychology (miscellaneous); General Psychology; Psychiatric Mental Health; Psychiatry and Mental Health; Social Sciences & Humanities; Sluggish cognitive tempo; procrastination; internalizing behavior problems; adolescents; executive function; TEMPO; VALIDITY; ADHD; PERFECTIONISM; CHILDREN; ANXIETY